2011
DOI: 10.1155/2011/935160
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in Transformation Induced by Metal Mixture

Abstract: Metals are ubiquitous pollutants present as mixtures. In particular, mixture of arsenic-cadmium-lead is among the leading toxic agents detected in the environment. These metals have carcinogenic and cell-transforming potential. In this study, we used a two step cell transformation model, to determine the role of oxidative stress in transformation induced by a mixture of arsenic-cadmium-lead. Oxidative damage and antioxidant response were determined. Metal mixture treatment induces the increase of damage marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Finally, we needed to elucidate whether the effects of miR-222 are relevant to the cellular transformation endpoint assessed by morphological changes and foci formation in Balb/c 3T3 model [39,48,57], we observed that the use of the pre-miR-222 as an initiator (combined with the known promoter TPA [56] accelerates transformation and generates foci on day 13 " Fig 5". Furthermore, pre-miR-222 also produce more foci number when it is used as a initiator and promoter stimulus, but not when is used only as a promoter stimulus (along with the known initiator agent MNNG [58,59]), confirming the cellular consequences of elevated levels of this miRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we needed to elucidate whether the effects of miR-222 are relevant to the cellular transformation endpoint assessed by morphological changes and foci formation in Balb/c 3T3 model [39,48,57], we observed that the use of the pre-miR-222 as an initiator (combined with the known promoter TPA [56] accelerates transformation and generates foci on day 13 " Fig 5". Furthermore, pre-miR-222 also produce more foci number when it is used as a initiator and promoter stimulus, but not when is used only as a promoter stimulus (along with the known initiator agent MNNG [58,59]), confirming the cellular consequences of elevated levels of this miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The two-stage Balb/c 3T3 cell assay was performed as described previously with slight modifications [48,49]. The transformation protocol consisted of 13 days, divided in two phases: initiation between days 1 to 7 and promotion between days 7 to 13.…”
Section: Two-stage Balb/c 3t3 Cell Assaymentioning
confidence: 99%
“…Decreased body weight gain in exposed animals relative to control indicated the growth retarding effect of the mixture of these three heavy metals on female albino rats. Reports suggested reduction in food and water intake might contribute to decrease in body weight gain in exposed animal 25 . The reduction of weight of reproductive organs ovary and uterus was indicative of toxic effect of the metal mixture on reproductive system of female rats treated with metal mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Low arsenic concentrations alter glucocorticoid signaling [135], function in oxidative stress [136], contribute to hypertension [137] and increase the risk of birth defects [138]. Arsenic also can induce cancer [137] and contributes to increased cardiovascular disease [139], skin lesions, diabetes, reproductive toxicity, neurologic disease and neurobehavioral disorders.…”
Section: Some Environmental Causes Of Epigenetic Changesmentioning
confidence: 99%
“…Sexual dimorphism may exist in the interaction between arsenic and dietary methyl donors [175]. Arsenic, other heavy metals and organic toxins may affect the epigenome via cellular responses to oxidative stress involving insulin signaling PPARγ-dependent pathways [136,139]. …”
Section: Some Environmental Causes Of Epigenetic Changesmentioning
confidence: 99%